2010
DOI: 10.1172/jci41196
|View full text |Cite
|
Sign up to set email alerts
|

α-1 Antitrypsin regulates human neutrophil chemotaxis induced by soluble immune complexes and IL-8

Abstract: Hereditary deficiency of the protein α-1 antitrypsin (AAT) causes a chronic lung disease in humans that is characterized by excessive mobilization of neutrophils into the lung. However, the reason for the increased neutrophil burden has not been fully elucidated. In this study we have demonstrated using human neutrophils that serum AAT coordinates both CXCR1-and soluble immune complex (sIC) receptor-mediated chemotaxis by divergent pathways. We demonstrated that glycosylated AAT can bind to IL-8 (a ligand for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

17
305
3
5

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 254 publications
(335 citation statements)
references
References 83 publications
17
305
3
5
Order By: Relevance
“…In contrast, however, LTB 4 did not bind the AAT cleavage product, C-36. Moreover, we have previously demonstrated the importance of AAT glycosylation motifs for IL-8 binding (29), but in contrast, results of the present study indicate that recombinant nonglycosylated AAT successfully binds LTB 4 . The representative UV spectra profiles in Fig.…”
contrasting
confidence: 99%
See 2 more Smart Citations
“…In contrast, however, LTB 4 did not bind the AAT cleavage product, C-36. Moreover, we have previously demonstrated the importance of AAT glycosylation motifs for IL-8 binding (29), but in contrast, results of the present study indicate that recombinant nonglycosylated AAT successfully binds LTB 4 . The representative UV spectra profiles in Fig.…”
contrasting
confidence: 99%
“…In light of our previous publications demonstrating the ability of AAT to inhibit IL-8-and TNF-a-induced neutrophil responses (28,29), we assessed the capacity of AAT to act as a novel LTB 4 antagonist. Initial studies examined the effect of AAT on neutrophil adhesion.…”
Section: Aat Modulates Ltb 4 -Induced Neutrophil Adhesion and Degranumentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, the absence of elastase had no effect on neutrophil recruitment (26), which supports our findings. Circulating AAT enters cells (27) and can act as an inhibitor for matriptase (28), caspases-1 and -3 (29,30), TNF-α-converting enzyme (31), and intracellular calpain I (32).…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, we showed that AAT reduced RANKL-induced TNF-α production. One possible mechanism is that AAT inhibits ADAM17, also known as a TNF-α-converting enzyme, which cleaves and releases soluble TNF-α (39). A recent study by Bergin et al (32) showed that AAT can reduce the binding of TNF-α to its receptors (TNFR1 and TNFR2).…”
Section: Aat Inhibited Catk Activity and Rankl-induced Catk Gene Exprmentioning
confidence: 99%